A method for preparing lithium aluminum titanium phosphate

CN120943230BActive Publication Date: 2026-10-09SHENZHEN CAPCHEM TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410590263.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-13
Publication Date
2026-10-09
Estimated Expiration
2044-05-13

AI Technical Summary

Technical Problem

[0005]本发明所要解决的技术问题是针对现有磷酸钛铝锂的制备方法存在使用设备能耗高、生产成本高的问题,本申请提供一种磷酸钛铝锂的制备方法

Benefits of technology

[0040]The preparation method provided in this application employs staged cooling. Multi-stage cooling helps optimize the crystal growth of lithium titanium aluminum phosphate, resulting in smaller and more uniform grain structures, increased density, elimination of residual gases, stable phase structure, and control of phase transition processes, leading to more stable microstructure and properties of the product. This improves the mechanical, electrochemical, and corrosion resistance of the lithium titanium aluminum phosphate material. The prepared lithium titanium aluminum phosphate powder exhibits high density and uniformity, small particle size reaching the nanoscale, excellent electrochemical performance, and good compatibility. The preparation method of lithium titanium aluminum phosphate provided in this application, after staged cooling and pulverization of the crude product, yields lithium titanium aluminum phosphate powder with high density and uniformity, small particle size reaching the nanoscale. The production process is simple and easy to control, requires less equipment investment, has low energy consumption, low cost, and is highly automated, making it easy to mass-produce lithium titanium aluminum phosphate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004837048470000121
    Figure BDA0004837048470000121
  • Figure BDA0004837048470000131
    Figure BDA0004837048470000131
Patent Text Reader

Abstract

In order to overcome the problems of high energy consumption and high production cost of the existing preparation method of lithium aluminum titanium phosphate, the application provides a preparation method of lithium aluminum titanium phosphate, comprising the following steps: pretreating a lithium source, an aluminum source and a titanium source, mixing the lithium source, the aluminum source and the titanium source after the pretreatment with a phosphorus source to obtain a crude product, and performing stage cooling and crushing on the crude product to obtain the product lithium aluminum titanium phosphate; the stage cooling is multi-stage cooling, and the multi-stage cooling comprises a first cooling stage, a second cooling stage, a third cooling stage, a fourth cooling stage, a fifth cooling stage, a sixth cooling stage and a seventh cooling stage. The preparation method of lithium aluminum titanium phosphate provided by the application obtains the product after the post-treatment of stage cooling and crushing on the crude product, and has the advantages of simple production process, easy control, low investment in equipment, low energy consumption, low cost, simple method, high automation degree and easy batch production of lithium aluminum titanium phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of secondary battery technology, specifically relating to a method for preparing lithium titanium aluminum phosphate. Background Technology

[0002] Lithium-ion batteries possess characteristics such as high operating voltage, high energy density, long cycle life, low self-discharge, no memory effect, and environmental friendliness, making them an ideal power source for mobile communications, power tools, medical devices, and other equipment. With the vigorous promotion of new energy vehicles both domestically and internationally, lithium-ion batteries, based on their unique advantages, have become the preferred power source for electric vehicles, thus demonstrating their broad development prospects.

[0003] Lithium titanium aluminum phosphate (LiTiAPO), a core component of all-solid-state batteries, still faces bottlenecks in its synthesis. Currently, commonly used methods for synthesizing LiTiAPO include solid-state sintering, liquid-phase precipitation, and sol-gel methods. However, these methods are complex, costly, and energy-intensive for industrial production. Developing a simple, low-cost, and energy-efficient production process is an urgent problem to be solved.

[0004] Lithium aluminum titanium phosphate has a typical NASICON structure and the molecular formula Li. 1+x Al x Ti 2-x (PO4)3 (0≤x≤0.5) possesses a series of advantages, including high room temperature ionic conductivity, low formulation cost, and high stability in air environment, making it suitable as a solid electrolyte for lithium-ion conduction. However, the preparation process is cumbersome, the equipment cost is high, and the energy consumption is high. Chinese invention patent CN116093421A discloses a method for preparing a high-density lithium titanium aluminum phosphate solid electrolyte material, but the practical application of the prepared high-density lithium titanium aluminum phosphate solid electrolyte material faces significant problems: the interface between lithium titanium aluminum phosphate and the lithium metal anode is extremely unstable and cannot be directly contacted. If direct contact occurs, lithium titanium aluminum phosphate will undergo TiO2 formation. 4+ To Ti 3+ The reduction reaction is irreversible; its structure also changes, the interface becomes unstable, leading to crack formation, reducing the ionic conductivity of the solid electrolyte, and causing battery failure. Simultaneously, the cracked interface has high electronic conductivity, which can lead to the formation of lithium dendrites, posing a serious safety hazard. Therefore, the preparation method mentioned in Chinese Patent CN116093421A requires further crushing into nanoparticles before use. Furthermore, the preparation process in Chinese Patent CN116093421A involves numerous equipment steps, such as two sand milling processes, two sintering processes, and one spray drying process, all of which have high energy consumption, resulting in extremely high industrial production costs. Summary of the Invention

[0005] The technical problem to be solved by the present invention is that the existing methods for preparing lithium titanium aluminum phosphate have problems such as high energy consumption of equipment and high production cost. This application provides a method for preparing lithium titanium aluminum phosphate.

[0006] To address the aforementioned technical problems, in a first aspect, this application provides a method for preparing lithium titanium aluminum phosphate, comprising the following steps:

[0007] The lithium source, aluminum source and titanium source are pretreated, and the pretreated lithium source, aluminum source and titanium source are mixed with phosphorus source and sintered to obtain crude product. The crude product is then subjected to staged cooling and pulverization to obtain the product lithium titanium aluminum phosphate.

[0008] The staged cooling is a multi-stage cooling process, which includes a first cooling stage, a second cooling stage, a third cooling stage, a fourth cooling stage, a fifth cooling stage, a sixth cooling stage, and a seventh cooling stage.

[0009] Preferably, the staged cooling of the crude product includes the following steps:

[0010] The crude product is subjected to a first cooling stage, a second cooling stage, a third cooling stage, a fourth cooling stage, a fifth cooling stage, a sixth cooling stage, and a seventh cooling stage in sequence.

[0011] The final temperature of the first cooling stage is T1, and the temperature is maintained at T1 for 20 to 40 minutes.

[0012] The final temperature of the second cooling stage is T2, and the temperature is maintained at T2 for 20 to 40 minutes.

[0013] The final temperature of the third cooling stage is T3, and the temperature is maintained at T3 for 20 to 40 minutes.

[0014] The final temperature of the fourth cooling stage is T4, and the temperature is maintained at T4 for 20 to 40 minutes.

[0015] The final temperature of the fifth cooling stage is T5, and the temperature is maintained at T5 for 20 to 40 minutes.

[0016] The final temperature of the sixth cooling stage is T6, and the temperature is maintained at T6 for 20 to 40 minutes.

[0017] The final temperature of the seventh cooling stage is T7;

[0018] T1 is 680-730℃, T2 is 580-630℃, T3 is 480-530℃, T4 is 380-430℃, T5 is 280-330℃, T6 is 180-230℃, and T7 is 25-35℃.

[0019] Preferably, the first cooling stage includes the following steps: the crude product is first cooled to a temperature of T1 at a first cooling rate V1, where the first cooling rate V1 is 10-15℃ / min; the second cooling stage includes the following steps: the crude product is first cooled to a temperature of T2 at a second cooling rate V2, where the second cooling rate V2 is 10-15℃ / min.

[0020] The third cooling stage includes the following steps: the crude product is first subjected to the third cooling stage at a third cooling rate V3 until the temperature is T3, and the third cooling rate V3 is 10-15℃ / min.

[0021] The fourth cooling stage includes the following steps: the crude product is first subjected to the fourth cooling stage at a fourth cooling rate V4 until the temperature is T4, where the fourth cooling rate V4 is 10-15℃ / min.

[0022] The fifth cooling stage includes the following steps: the crude product is first subjected to the fifth cooling stage at a fifth cooling rate V5 until the temperature is T5, and the fifth cooling rate V5 is 10-15℃ / min.

[0023] Preferably, the sixth cooling stage includes the following steps: the crude product is first subjected to the sixth cooling stage at a sixth cooling rate V6 until the temperature is T6, wherein the sixth cooling rate V6 is 20-30℃ / min;

[0024] The seventh cooling stage includes the following steps: the crude product is first subjected to the seventh cooling stage at a seventh cooling rate V7 until the temperature is T7, and the seventh cooling rate V7 is 20-30℃ / min.

[0025] Preferably, the pretreatment of the lithium source, aluminum source and titanium source includes the following steps: the lithium source, aluminum source and titanium source are pulverized by airflow, and the particle size D50 of the pulverized particles is 500-1000 nm.

[0026] Preferably, the molar ratio of lithium source, aluminum source, titanium source and phosphorus source is (1+x):x:(2-x):3;

[0027] Where x is 0.3 to 0.5.

[0028] Preferably, the step of mixing the lithium source, aluminum source, and titanium source after pretreatment with the phosphorus source for sintering includes the following steps:

[0029] After the pretreatment is completed, the lithium source, aluminum source and titanium source are mixed with the phosphorus source and pressed under a pressure of 200-20000N. After pressing, the first stage sintering and the second stage sintering are carried out in sequence.

[0030] In the first stage of sintering, the first sintering temperature is 400–450℃ and the first sintering time is 1.5–2.5 h;

[0031] In the second stage of sintering, the second sintering temperature is 800-920℃ and the second sintering time is 4-7h.

[0032] Preferably, the first stage sintering includes the following steps: first heating to the first sintering temperature at a first heating rate, and performing the first stage sintering within a first sintering time, wherein the first heating rate is 4 to 6 °C / min;

[0033] After the first stage of sintering is completed, the waste is discharged, and then the second stage of sintering is carried out. The second stage of sintering includes the following steps: heating to the second sintering temperature at a second heating rate and carrying out the second stage of sintering within a second sintering time. The second heating rate is 2 to 4 °C / min.

[0034] Preferably, the process of pulverizing to obtain lithium titanium aluminum phosphate includes the following steps: subjecting the product obtained after staged cooling to a first pulverization process and a second pulverization process to obtain the product lithium titanium aluminum phosphate; the D50 particle size of the product lithium titanium aluminum phosphate is 600-800 nm.

[0035] And / or, the primary crushing process includes roller crushing; the secondary crushing process includes airflow crushing.

[0036] Preferably, the lithium source includes one or more of LiOH, Li2CO3, Li2SO4, CH3COOLi, and LiNO3;

[0037] The aluminum source includes one or more of Al2(SO4)3·18H2O, Al2O3, Al(OH)3, and Al2(CO3)3;

[0038] The titanium source includes TiCl4 and anatase TiO2. 2, One or more of the following: diamond-type TiO2;

[0039] The phosphorus source includes one or more of (NH4)2HPO4, NH4H2PO4, and (NH4)3PO4.

[0040] The preparation method provided in this application employs staged cooling. Multi-stage cooling helps optimize the crystal growth of lithium titanium aluminum phosphate, resulting in smaller and more uniform grain structures, increased density, elimination of residual gases, stable phase structure, and control of phase transition processes, leading to more stable microstructure and properties of the product. This improves the mechanical, electrochemical, and corrosion resistance of the lithium titanium aluminum phosphate material. The prepared lithium titanium aluminum phosphate powder exhibits high density and uniformity, small particle size reaching the nanoscale, excellent electrochemical performance, and good compatibility. The preparation method of lithium titanium aluminum phosphate provided in this application, after staged cooling and pulverization of the crude product, yields lithium titanium aluminum phosphate powder with high density and uniformity, small particle size reaching the nanoscale. The production process is simple and easy to control, requires less equipment investment, has low energy consumption, low cost, and is highly automated, making it easy to mass-produce lithium titanium aluminum phosphate. Detailed Implementation

[0041] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0042] This application provides a method for preparing lithium titanium aluminum phosphate, comprising the following steps:

[0043] The lithium source, aluminum source and titanium source are pretreated, and the pretreated lithium source, aluminum source and titanium source are mixed with phosphorus source and sintered to obtain crude product. The crude product is then subjected to staged cooling and pulverization to obtain the product lithium titanium aluminum phosphate.

[0044] The staged cooling is a multi-stage cooling process, which includes a first cooling stage, a second cooling stage, a third cooling stage, a fourth cooling stage, a fifth cooling stage, a sixth cooling stage, and a seventh cooling stage.

[0045] Specifically, the preferred pretreatment is air jet milling, such as adding lithium, aluminum and titanium sources to an air jet mill for pulverization.

[0046] Specifically, the cooling process is a multi-stage cooling method, which includes a first cooling stage, a second cooling stage, a third cooling stage, a fourth cooling stage, a fifth cooling stage, a sixth cooling stage, and a seventh cooling stage. Preferably, the crude product is subjected to the first cooling stage, the second cooling stage, the third cooling stage, the fourth cooling stage, the fifth cooling stage, the sixth cooling stage, and the seventh cooling stage in sequence.

[0047] The method for preparing lithium titanium aluminum phosphate provided in this application includes a multi-stage cooling process, which includes a seven-stage cooling process. It is understood that the multi-stage cooling process can also be more than seven stages, such as an eight-stage cooling process or a nine-stage cooling process.

[0048] The product obtained by pulverization is lithium titanium aluminum phosphate. After staged cooling, the lithium titanium aluminum phosphate can be pulverized to the nanoscale with small particle size, which can be directly used in the next step, while reducing energy consumption and equipment costs, and reducing production costs.

[0049] The preparation method provided in this application employs staged cooling. This multi-stage cooling approach helps optimize the crystal growth of lithium titanium aluminum phosphate (LFP) materials, resulting in smaller and more uniform grain structures, increased density, elimination of residual gases, stable phase structure, and control of phase transition processes. This leads to more stable microstructure and properties of the product, improving the mechanical, electrochemical, and corrosion resistance of the LFP material. The prepared LFP powder exhibits high density and uniformity, small particle size (reaching the nanoscale), excellent electrochemical performance, and good compatibility. The LFP preparation method provided in this application involves staged cooling and pulverization of the crude product to obtain the final product. The production process is simple and easy to control, requires minimal equipment investment, has low energy consumption, low cost, and is highly automated, making LFP easy to mass-produce.

[0050] In some embodiments, the staged cooling of the crude product includes the following steps:

[0051] The crude product is subjected to a first cooling stage, a second cooling stage, a third cooling stage, a fourth cooling stage, a fifth cooling stage, a sixth cooling stage, and a seventh cooling stage in sequence.

[0052] The final temperature of the first cooling stage is T1, and the temperature is maintained at T1 for 20 to 40 minutes.

[0053] The final temperature of the second cooling stage is T2, and the temperature is maintained at T2 for 20 to 40 minutes.

[0054] The final temperature of the third cooling stage is T3, and the temperature is maintained at T3 for 20 to 40 minutes.

[0055] The final temperature of the fourth cooling stage is T4, and the temperature is maintained at T4 for 20 to 40 minutes.

[0056] The final temperature of the fifth cooling stage is T5, and the temperature is maintained at T5 for 20 to 40 minutes.

[0057] The final temperature of the sixth cooling stage is T6, and the temperature is maintained at T6 for 20 to 40 minutes.

[0058] The final temperature of the seventh cooling stage is T7;

[0059] T1 is 680-730℃, T2 is 580-630℃, T3 is 480-530℃, T4 is 380-430℃, T5 is 280-330℃, T6 is 180-230℃, and T7 is 25-35℃.

[0060] Specifically, the key to setting up multi-stage cooling is to implement seven stages of cooling in sequence, and the corresponding cooling rate for each stage.

[0061] The multi-stage cooling process after sintering, from the first to the seventh cooling stages, has the following effects: 1) Reduces stress concentration and cracking risk. Rapid cooling can lead to internal and external temperature differences, causing stress concentration and product cracking. Staged cooling can prevent product cracking; 2) Optimizes crystal growth, resulting in smaller and more uniform grain structures, higher density, and better mechanical strength; 3) Increases density, eliminates residual gases, and improves mechanical properties, electrical properties, and corrosion resistance; 4) Stabilizes the phase structure, controlling the phase transformation process to make the product's microstructure and performance more stable.

[0062] In some embodiments, the first cooling stage includes the following steps: the crude product is first cooled to a temperature of T1 at a first cooling rate V1, where the first cooling rate V1 is 10-15°C / min.

[0063] The second cooling stage includes the following steps: the crude product is first subjected to a second cooling stage at a second cooling rate V2 until the temperature is T2, where the second cooling rate V2 is 10-15℃ / min;

[0064] The third cooling stage includes the following steps: the crude product is first subjected to the third cooling stage at a third cooling rate V3 until the temperature is T3, and the third cooling rate V3 is 10-15℃ / min.

[0065] The fourth cooling stage includes the following steps: the crude product is first subjected to the fourth cooling stage at a fourth cooling rate V4 until the temperature is T4, where the fourth cooling rate V4 is 10-15℃ / min.

[0066] The fifth cooling stage includes the following steps: the crude product is first subjected to the fifth cooling stage at a fifth cooling rate V5 until the temperature is T5, and the fifth cooling rate V5 is 10-15℃ / min.

[0067] Specifically, the cooling rates for the first to fifth cooling stages are all the same, ranging from 10 to 15 °C / min. This helps reduce stress concentration and cracking risk, optimize crystal growth, and obtain smaller and more uniform grain structures with higher density and better mechanical strength. It also improves density, eliminates residual gases, enhances mechanical properties, electrical properties, and corrosion resistance, and stabilizes the phase structure. Specifically, the cooling rates for the first to fifth cooling stages can be 10 °C / min, 10.5 °C / min, 11 °C / min, 11.5 °C / min, 12 °C / min, 12.5 °C / min, 13 °C / min, 13.5 °C / min, 14 °C / min, 14.5 °C / min, and 15 °C / min, etc.

[0068] If the cooling rate from the first to the fifth cooling stage exceeds 10-15℃ / min, rapid cooling will cause a temperature difference between the inside and outside, leading to stress concentration, which may result in product cracking, even breakage, larger crystals, low mechanical strength, low density, even pores, poor electrochemical performance, poor corrosion resistance, unstable microstructure, and product inhomogeneity. If the cooling rate is too fast, it will also cause more product to adhere to the sagger after finishing, resulting in a lower yield and thus affecting the service life of the sagger.

[0069] In some embodiments, the sixth cooling stage includes the following steps: the crude product is first subjected to the sixth cooling stage at a sixth cooling rate V6 until the temperature is T6, wherein the sixth cooling rate V6 is 20-30℃ / min;

[0070] The seventh cooling stage includes the following steps: the crude product is first subjected to the seventh cooling stage at a seventh cooling rate V7 until the temperature is T7, where the seventh cooling rate V7 is 20-30℃ / min.

[0071] Specifically, the cooling rates in the sixth and seventh cooling stages are both 20–30 °C / min, which also help reduce stress concentration and cracking risk, optimize crystal growth, obtain smaller and more uniform grain structures, higher density and better mechanical strength; improve density, eliminate residual gases, enhance mechanical properties, electrical properties and corrosion resistance; and stabilize the phase structure. Specifically, the cooling rates in the sixth and seventh cooling stages can be 20 °C / min, 20.3 °C / min, 20.5 °C / min, 21 °C / min, 22 °C / min, 23 °C / min, 24 °C / min, 25 °C / min, 26 °C / min, 27 °C / min, 28 °C / min, 29 °C / min, 30 °C / min, etc.

[0072] In some embodiments, the pretreatment of the lithium source, aluminum source and titanium source includes the following steps: pulverizing the lithium source, aluminum source and titanium source by airflow, and the pulverized particles have a D50 particle size of 500-1000 nm.

[0073] Specifically, lithium, aluminum, and titanium sources are pulverized using airflow. For example, lithium, aluminum, and titanium sources can be fed into an airflow pulverizer for pulverization. The particle size of the pulverized particles is 500-1000 nm. The small particle size helps to mix the lithium, aluminum, and titanium sources evenly, increases the specific surface area, and helps to fully sinter to form lithium titanium aluminum phosphate with excellent mechanical properties.

[0074] Specifically, the particle size of the pulverized particles can be in the following ranges: 500nm~600nm, 600nm~700nm, 700nm~800nm, 800nm~900nm, 900nm~1000nm.

[0075] In some embodiments, the molar ratio of lithium source, aluminum source, titanium source and phosphorus source is (1+x):x:(2-x):3; where x is 0.3 to 0.5.

[0076] Specifically, x can be in the range of 0.3 to 0.4 or 0.4 to 0.5.

[0077] In some embodiments, the process of mixing the lithium source, aluminum source, and titanium source after pretreatment with a phosphorus source for sintering includes the following steps:

[0078] After the pretreatment, the lithium source, aluminum source, and titanium source are mixed with the phosphorus source and pressed under a pressure of 200-20000N. After pressing, the first stage sintering and the second stage sintering are carried out in sequence.

[0079] In the first stage of sintering, the first sintering temperature is 400–450℃ and the first sintering time is 1.5–2.5 h;

[0080] In the second stage of sintering, the second sintering temperature is 800-920℃ and the second sintering time is 4-7h.

[0081] Specifically, after pretreatment, the mixture is mixed with the phosphorus source and transferred to a 30cm*30cm crucible for pressing, with the pressure controlled at 200-20000N. Pressing can increase the single loading capacity without affecting the uniformity during sintering, and also reduces energy consumption during sintering. In essence, pressing involves mixing the pretreated mixture of lithium, aluminum, and titanium sources with the phosphorus source, and then pressing it into sheets or blocks under a pressure of 200-20000N. This pressing facilitates subsequent loading and sintering.

[0082] Sintering includes a first-stage sintering and a second-stage sintering. The first-stage sintering removes the water of crystallization from the lithium, aluminum, titanium, and phosphorus sources, as well as the ammonia gas generated during sintering, improving the uniformity and density during sintering. The second-stage sintering helps improve the density and uniformity of the solid electrolyte powder, resulting in better powder compatibility.

[0083] If the sintering temperature in the first stage is too low, the water of crystallization in the precursors such as phosphorus source cannot be completely removed, affecting the density and uniformity of lithium titanium aluminum phosphate; if the sintering temperature in the second stage is too high, the impurity content of the generated lithium titanium aluminum phosphate will increase.

[0084] In some embodiments, the first stage sintering includes the following steps: first heating to the first sintering temperature at a first heating rate, and performing first stage sintering within a first sintering time, wherein the first heating rate is 4 to 6 °C / min.

[0085] After the first stage of sintering is completed, the waste is discharged, and then the second stage of sintering is carried out. The second stage of sintering includes the following steps: heating to the second sintering temperature at a second heating rate and carrying out the second stage of sintering within a second sintering time. The second heating rate is 2 to 4 °C / min.

[0086] Specifically, the waste gases include water of crystallization and ammonia generated from lithium, aluminum, titanium and phosphorus sources.

[0087] In the first-stage sintering process, the temperature is raised to the first sintering temperature at a first heating rate. The temperature increase is slow, which effectively removes the water of crystallization from the lithium, aluminum, titanium, and phosphorus sources. In the second-stage sintering process, the temperature is raised to the second sintering temperature at a second heating rate. The lower heating rate is conducive to the complete sintering of the lithium, aluminum, titanium, and phosphorus sources, improving the powder density and uniformity of lithium titanium aluminum phosphate and resulting in better compatibility.

[0088] In some embodiments, the process of pulverizing to obtain lithium titanium aluminum phosphate includes the following steps: subjecting the product obtained after staged cooling to a first pulverization process and a second pulverization process to obtain lithium titanium aluminum phosphate; the D50 particle size of the lithium titanium aluminum phosphate is 600-800 nm.

[0089] Specifically, the primary crushing process involves initially pulverizing and refining the product obtained after staged cooling. The secondary crushing process further pulverizes the particles based on the primary crushing process, resulting in nano-sized lithium titanium aluminum phosphate products that can be used directly as solid electrolytes.

[0090] In some embodiments, the primary crushing process includes roller crushing; the secondary crushing process includes airflow crushing.

[0091] Specifically, using air jet milling instead of spray drying greatly reduces energy consumption and equipment costs, thus lowering the cost of industrial production.

[0092] Compared with existing technologies, the preparation method of lithium titanium aluminum phosphate provided in this application simplifies the production process, reduces the equipment required in the preparation process, improves the degree of automation, reduces energy consumption in the preparation process, increases the production capacity of industrial-scale preparation of lithium titanium aluminum phosphate nanopowder, and at the same time improves the powder density and uniformity of lithium titanium aluminum phosphate, and the powder has better compatibility.

[0093] In some embodiments, the lithium source includes one or more of LiOH, Li2CO3, Li2SO4, CH3COOLi, and LiNO3.

[0094] In some embodiments, the aluminum source includes one or more of Al2(SO4)3·18H2O, Al2O3, Al(OH)3, and Al2(CO3)3.

[0095] In some embodiments, the titanium source includes TiCl4 and anatase TiO2. 2, One or more of the diamond-type TiO2.

[0096] In some embodiments, the phosphorus source includes one or more of (NH4)2HPO4, NH4H2PO4, and (NH4)3PO4.

[0097] Secondly, this application provides a method for preparing lithium titanium aluminum phosphate and its application in lithium-ion batteries, lithium-ion solid-state batteries, and lithium metal solid-state batteries.

[0098] Specifically, the preparation method of lithium titanium aluminum phosphate disclosed in this invention includes the following steps:

[0099] Example 1

[0100] 1) Precursor pretreatment:

[0101] Prepare lithium, aluminum, titanium and phosphorus sources according to the molar ratio Li:Al:Ti:P=(1+x):x:(2-x):3, where x is 0.4.

[0102] The lithium source was Li₂CO₃, the aluminum source was Al₂O₃ and Al(OH)₃, the titanium source was diamond-type TiO₂, and the phosphorus source was (NH₄)₂HPO₄. The lithium, aluminum, and titanium sources were respectively fed into an air jet mill for air jet milling, and the particle size of the pulverized particles reached 800 nm.

[0103] 2) Mixed pressing:

[0104] The pulverized lithium, aluminum, titanium, and phosphorus sources are fed into a high-speed mixer for thorough mixing to obtain a mixture. The mixture is then transferred to a 30*30cm crucible for pressing, with the pressure controlled at 200N.

[0105] 3) Sintering:

[0106] The mixture after tableting in step 2) is placed in a calcining furnace and heated at a first heating rate of 5℃ / min. After the temperature reaches the first sintering temperature of 450℃, the first stage of sintering is carried out for 2 hours.

[0107] After the first stage of sintering, the water of crystallization and ammonia gas in the precursor were removed. The temperature was then increased to a second sintering temperature of 920℃ at a second heating rate of 3℃ / min, and the second stage of sintering was carried out within a second sintering time of 5 hours. After sintering, a crude product was obtained.

[0108] 4) Staged cooling

[0109] The crude product is subjected to a first cooling stage, a second cooling stage, a third cooling stage, a fourth cooling stage, a fifth cooling stage, a sixth cooling stage, and a seventh cooling stage in sequence.

[0110] The crude product was first cooled to T1 of 730℃ at a rate of 10℃ / min using the first cooling stage, and then held for 40 minutes.

[0111] After the first cooling stage is completed, the crude product is subjected to a second cooling stage at a rate of V2 of 10℃ / min, and the temperature is reduced to T2 of 630℃ and held for 40 minutes.

[0112] After the second cooling stage is completed, the crude product is subjected to the third cooling stage at a rate of 10℃ / min (V3) to reduce the temperature to T3 of 530℃ and hold for 30 minutes.

[0113] After the third cooling stage is completed, the crude product is first subjected to the fourth cooling stage at a rate of 10℃ / min (V4) to reduce the temperature to T4 of 400℃ and hold for 30 minutes.

[0114] After the fourth cooling stage, the crude product is subjected to the fifth cooling stage at a rate of 10℃ / min (V5) to reduce the temperature to 300℃ (T5) and held for 30 minutes.

[0115] After the fifth cooling stage, the crude product is subjected to the sixth cooling stage at a rate of 20℃ / min (V6) to reduce the temperature to 230℃ (T6) and held for 20 minutes.

[0116] After the sixth cooling stage, the crude product is subjected to the seventh cooling stage at a rate of 20℃ / min (V7) until the temperature is reduced to T7 (25±5℃, room temperature), and the cooling process ends.

[0117] 5) After crushing and processing, the product lithium titanium aluminum phosphate is obtained:

[0118] The product obtained after cooling in step 4) is subjected to a first pulverization process and a second pulverization process to obtain the product lithium titanium aluminum phosphate; the D50 particle size of the product lithium titanium aluminum phosphate is 800nm.

[0119] The primary crushing process is roller crushing; the secondary crushing process is air jet crushing.

[0120] Example 2

[0121] This embodiment is the same as most of the steps in Embodiment 1, except that the lithium source selected in step 1) is changed to a ratio of LiOH:Li2CO3 = 5:5, and the rest is the same as in Embodiment 1.

[0122] Example 3

[0123] This embodiment is the same as most of the steps in Embodiment 1, except that the aluminum source selected in step 1) is changed to Al2(SO4)3·18H2O, and the rest is the same as in Embodiment 1.

[0124] Example 4

[0125] This embodiment is the same as embodiment 1 in most steps, except that the second sintering temperature in step 4) is 950°C and the cooling rate V5 in the fifth cooling stage is 25°C / min. The rest is the same as in embodiment 1.

[0126] Example 5

[0127] This embodiment is the same as most of the steps in Embodiment 1, except that the phosphorus source selected in step 1) is changed to NH4H2PO4, and the rest is the same as in Embodiment 1.

[0128] Example 6

[0129] This embodiment is the same as most of the steps in Embodiment 1. The difference is that the second sintering temperature in step 4) is 1000℃, and the cooling rate V5 in the fifth cooling stage is changed to 15℃ / min. The rest is the same as in Embodiment 1.

[0130] Example 7

[0131] This embodiment is the same as most of the steps in embodiment 1, except that the first sintering time in step 3) is 1 hour, and the rest is the same as in embodiment 1.

[0132] Example 8

[0133] This embodiment is the same as embodiment 1 in most steps, except that in step 4), V1, V2, V3, V4, and V5 are all 15℃ / min; V6 and V7 are 30℃ / min; the rest is the same as in embodiment 1.

[0134] Example 9

[0135] This embodiment is the same as embodiment 1 in most steps, except that in step 4), T1 is 680℃, T2 is 580℃, T3 is 480℃, T4 is 380℃, T5 is 280℃, and T6 is 180℃; the rest is the same as in embodiment 1.

[0136] Example 10

[0137] This embodiment is the same as embodiment 1 in most steps, except that in step 4), V1, V2, V3, V4, and V5 are all at 20°C / min, and V6 and V7 are both at 35°C / min. The rest is the same as in embodiment 1.

[0138] Example 11

[0139] This embodiment is the same as embodiment 1 in most steps, except that in step 4), V1, V2, V3, V4, and V5 are all 5℃ / min, and V6 and V7 are both 15℃ / min. The rest is the same as in embodiment 1.

[0140] Example 12

[0141] This embodiment is the same as embodiment 1 in most steps, except that in step 3), the first sintering temperature is 400°C and the second sintering temperature is 800°C.

[0142] Example 13

[0143] This embodiment is the same as most of the steps in embodiment 1, except that the first sintering temperature in step 3) is 300°C.

[0144] Example 14

[0145] This embodiment is the same as most of the steps in embodiment 1, except that the particle size D50 of the pulverized particles in step 1) precursor pretreatment step reaches 2000nm.

[0146] Example 15

[0147] This embodiment is the same as most of the steps in embodiment 1, except that in step 5), there is no first crushing, but a second crushing is performed directly.

[0148] Example 16

[0149] This embodiment is the same as most of the steps in embodiment 1. The difference is that in step 3), there is no first-stage sintering. The temperature is directly increased to 920°C at 5°C / min and sintered for 7 hours. The rest is the same as in embodiment 1.

[0150] Comparative Example 1

[0151] This comparative example is the same as most of the steps in Example 1, except that Comparative Example 1 does not have the step of "putting the lithium source, aluminum source and titanium source into the air jet mill for air jet milling".

[0152] Comparative Example 2

[0153] This comparative example is the same as most of the steps in Example 1, except that the cooling step in step 4) is different, as detailed below.

[0154] The crude product is first subjected to a first cooling stage, with the temperature reduced to 300℃ at a cooling rate of 10℃ / min.

[0155] After the first cooling stage is completed, the second cooling stage is carried out, and the temperature is reduced to 25±5℃ (room temperature) at a cooling rate of 20℃ / min, and the cooling is completed.

[0156] The rest is the same as in Example 1.

[0157] Comparative Example 3

[0158] This comparative example is the same as Example 1 in most steps, except that step 5) does not include the post-processing step of roller crushing. The rest is the same as Example 1.

[0159] The particle size of the products prepared in the above embodiments and comparative examples was tested. The residual product stuck to the sagger wall after the product was removed was scraped off with a tool, weighed, and the weight percentage of the residual product in the sagger was calculated.

[0160] Method for calculating the proportion of residual material in the crucible:

[0161] W1 weighs the product removed from the weighing sagger.

[0162] W2 weighs the residual product that adheres to the sagger wall after the product is removed from the weighing sagger.

[0163] X represents the weight percentage of the product remaining in the sagger.

[0164] X = W2 / (W 1+ W2)

[0165] The test results are shown in Table 1.

[0166] Table 1

[0167]

[0168]

[0169] As shown in Table 1, compared with Comparative Example 1, Example 1, without the pretreatment airflow pulverization step for lithium, aluminum, and titanium sources, had a larger weight percentage (X) of residual product in the crucible and a larger particle size (D50). This indicates that performing airflow pulverization pretreatment on the lithium, aluminum, and titanium sources before sintering helps to mix them uniformly, improves the specific surface area, reduces the risk of product cracking during sintering, optimizes crystal growth, and obtains a smaller and more uniform grain structure. Comparing Example 1 with Comparative Example 2, after sintering, only two cooling cycles were performed, resulting in a larger amount of residual product in the crucible (X being the largest) and a higher D50. This indicates that the lithium titanium aluminum phosphate prepared using the cooling method described in this application has high powder density and uniformity, small particle size reaching the nanoscale, excellent electrochemical performance, and good compatibility. Comparing Example 1 with Comparative Example 3, the pulverization treatment after cooling helps to obtain nanoscale lithium titanium aluminum phosphate products that can be directly used as solid electrolytes. Comparing Example 1 and Example 15, the product obtained without primary pulverization has a larger particle size D50, indicating that the product obtained by primary and secondary pulverization is nanoscale and can be directly used as a solid electrolyte.

[0170] Comparing Examples 1-3 and 5, changing the types of lithium, aluminum, and phosphorus sources resulted in similar weight percentage (X) of the residual product in the crucible and similar particle size (D50). This indicates that as long as the types of lithium, aluminum, phosphorus, and titanium sources added meet the requirements of this application, they will have the same effect. Comparing Examples 1, 4, and 6, a second sintering temperature higher than 800–920°C resulted in a larger D50 particle size of the obtained lithium titanium aluminum phosphate product. This suggests that a second-stage sintering temperature of 800–920°C and a second sintering time of 4–7 hours help improve the powder density and uniformity of the electrolyte, resulting in smaller particle sizes. Comparing Examples 1 and 12 with Examples 7 and 13, the first sintering time in Example 7 was too short, and the first sintering temperature in Example 13 was too low, both showing large values ​​(X). This indicates that both a short first sintering time and / or a low first sintering temperature easily lead to product cracking and affect crystal synthesis. A first sintering temperature of 400–450℃ and a first sintering time of 1.5–2.5 h help improve the uniformity and density during sintering. A comparison between Examples 1 and 16 shows that performing both first-stage and second-stage sintering helps obtain products with high powder density and uniformity, and small particle size.

[0171] Comparing Example 1 and Example 14, the lithium source, aluminum source and titanium source were subjected to air jet milling. The particle size D50 of the air jet milling was in the range of 500 to 1000 nm. The small particle size of the milled particles helped to mix the lithium source, aluminum source and titanium source evenly, increase the specific surface area, and help to improve the uniformity and density during sintering.

[0172] Comparing Examples 1, 8-9 and Example 10, the larger X value in Example 10 indicates that the cooling rate is too fast, which can easily cause the product to crack or even break, and the crystals to be larger. This shows that the lithium aluminum titanium phosphate powder prepared by the multi-stage cooling method provided in this application has high powder density and uniformity, small particle size reaching the nanoscale, excellent electrochemical performance, and good compatibility.

[0173] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing lithium titanium aluminum phosphate, characterized in that, Includes the following steps: The lithium source, aluminum source and titanium source are pretreated, and the pretreated lithium source, aluminum source and titanium source are mixed with phosphorus source and sintered to obtain crude product. The crude product is then subjected to staged cooling and pulverization to obtain the product lithium titanium aluminum phosphate. The staged cooling is a multi-stage cooling process, which includes a first cooling stage, a second cooling stage, a third cooling stage, a fourth cooling stage, a fifth cooling stage, a sixth cooling stage, and a seventh cooling stage. The first cooling stage includes the following steps: the crude product is first subjected to a first cooling stage at a first cooling rate V1 until the temperature reaches T1, and then held at T1 temperature for 20-40 minutes. The first cooling rate V1 is 10-15℃ / min. The second cooling stage includes the following steps: the crude product is first subjected to the second cooling stage at a second cooling rate V2 until the temperature is T2, and then kept at the temperature of T2 for 20~40 min. The second cooling rate V2 is 10~15℃ / min. The third cooling stage includes the following steps: the crude product is first subjected to the third cooling stage at a third cooling rate V3 until the temperature is T3, and then kept at the temperature of T3 for 20~40 min. The third cooling rate V3 is 10~15℃ / min. The fourth cooling stage includes the following steps: the crude product is first subjected to the fourth cooling stage at a fourth cooling rate V4 until the temperature is T4, and then kept at the T4 temperature for 20~40 min. The fourth cooling rate V4 is 10~15℃ / min. The fifth cooling stage includes the following steps: the crude product is first subjected to the fifth cooling stage at the fifth cooling rate V5 until the temperature is T5, and then kept at the temperature of T5 for 20~40 min. The fifth cooling rate V5 is 10~15℃ / min. The sixth cooling stage includes the following steps: the crude product is first subjected to the sixth cooling stage at a sixth cooling rate V6 until the temperature is T6, and then kept at the T6 temperature for 20~40 min. The sixth cooling rate V6 is 20~30℃ / min. The seventh cooling stage includes the following steps: the crude product is first subjected to the seventh cooling stage at a seventh cooling rate V7 until the temperature is T7, where the seventh cooling rate V7 is 20~30℃ / min; T1 is 680-730℃, T2 is 580-630℃, T3 is 480-530℃, T4 is 380-430℃, T5 is 280-330℃, T6 is 180-230℃, and T7 is 25-35℃; The pretreatment of the lithium source, aluminum source and titanium source includes the following steps: the lithium source, aluminum source and titanium source are pulverized by airflow, and the particle size D50 of the pulverized particles is 500~1000nm.

2. The method for preparing lithium titanium aluminum phosphate according to claim 1, characterized in that, The molar ratio of lithium source, aluminum source, titanium source and phosphorus source is (1+x):x:(2-x):3; Where x is 0.3 to 0.

5.

3. The method for preparing lithium titanium aluminum phosphate according to claim 1, characterized in that, The step of mixing the lithium source, aluminum source, and titanium source with the phosphorus source after pretreatment and then sintering includes the following steps: After the pretreatment is completed, the lithium source, aluminum source and titanium source are mixed with the phosphorus source and pressed under a pressure of 200~20000N. After pressing, the first stage sintering and the second stage sintering are carried out in sequence. In the first stage of sintering, the first sintering temperature is 400~450℃ and the first sintering time is 1.5~2.5h; The second sintering temperature in the second stage is 800~920℃ and the second sintering time is 4~7h.

4. The method for preparing lithium titanium aluminum phosphate according to claim 3, characterized in that, The first stage of sintering includes the following steps: first heating to the first sintering temperature at a first heating rate, and performing the first stage of sintering within a first sintering time, wherein the first heating rate is 4~6℃ / min; After the first stage of sintering is completed, the waste is discharged, and then the second stage of sintering is carried out. The second stage of sintering includes the following steps: heating to the second sintering temperature at a second heating rate and carrying out the second stage of sintering within a second sintering time. The second heating rate is 2~4℃ / min.

5. The method for preparing lithium titanium aluminum phosphate according to claim 1, characterized in that, The process of pulverizing lithium titanium aluminum phosphate includes the following steps: subjecting the product obtained after staged cooling to a first pulverization process and a second pulverization process to obtain the product lithium titanium aluminum phosphate; the D50 particle size of the product lithium titanium aluminum phosphate is 600~800nm. And / or, the primary crushing process includes roller crushing; the secondary crushing process includes airflow crushing.

6. The method for preparing lithium titanium aluminum phosphate according to claim 1, characterized in that, The lithium source includes one or more of LiOH, Li2CO3, Li2SO4, CH3COOLi, and LiNO3; The aluminum source includes one or more of Al2(SO4)3•18H2O, Al2O3, Al(OH)3, and Al2(CO3)3; The titanium source includes one or more of TiCl4 and anatase TiO2; The phosphorus source includes one or more of (NH4)2HPO4, NH4H2PO4, and (NH4)3PO4.

Citation Information

Patent Citations

  • Preparation method of LATP electrolyte powder, electrolyte sheet and all-solid-state battery

    CN115557483A

  • Preparation method of high-density lithium aluminum titanium phosphate solid electrolyte material

    CN116093421A